Delineation of groundwater potential area (GWP) using Analytical Hierarchy Process (AHP) and Fuzzy Analytical Hierarchy Process (FAHP) Method in Kedah / Nur lzzati Atiqah Mohd Rodzi - Mohd Rodzi, Nur lzzati Atiqah (2023)
The availability of groundwater is declining today, which has led to an increase in water demand. One of the main sources that significantly contribute to the annual total supply is groundwater. Water supply and demand have increased as a result of the rapid population growth, urbanization, agricultural development, and industrialization. Therefore, the objective of this study, that was conducted in Kedah, Malaysia, was to determine groundwater potential zones using approach of the Analytical Hierarchy Process (AHP) and Fuzzy Analytical Hierarchy Process (FAHP). Land use, soil, slope, elevation, rainfall, aspect, drainage density, geology, geomorphology, topographic wetness index (TWI), tube well, distance to fault, plan curvature, aquifer and lithology are among the 15 groundwater conditioning factors that were considered. All the parameters thematic layer were ultimately combined by a weighted sum overly analysis in a GIS environment using relative weights derived from the AHP and FAHP. The findings of this study displayed in maps of groundwater potential zones that classify as high, moderate and low. This study reveals that the FAHP method is more efficient in delineating GWPZ in this region with an accuracy of 91.7% better than AHP method at 90.2%. The findings of this study hold significant value for water management authorities, as it provides crucial insights for efficient planning, development and ensuring the long-term sustainability of our precious water resources.